IMPROVEMENT OF PRODUCTION TECHNOLOGY OF HIGH-QUALITY ROLLED WIRE - A. B. Sychkov; M. A. Zhigarev; S. Ju. Zhukova; A. V. Perchatkin; A. V. Peregudov (Литьë и металлургия)
Short results of the researches, carried out in the conditions of OAO «Moldavian metallurgical works» for recent 25 years and allowed to develop scientifically grounded technological decisions on increase of qualitative characteristics of rolled wire of wide branded grade, are given.